(untitled) (Journal of Rangpur Medical College, 2024)
Background: Vitamin D deficiency is common in the Middle East. To maintain health, vitamin D holds a very important place. Its deficiency is a major global health problem and affects both genders at all stages of life. Lack of exposure to sunlight is among the foremost causes of vitamin D deficiency. Methods: This hospital based cross sectional observational study carried out in the Department of Medicine in Comilla Medical College Hospital, Comilla, with a total of 100 cases purposively selected for the study. Detailed information was obtained in each individual according to protocol. Complete history was taken from patients. Thorough clinical examinations were done. Relevant investigations reports were collected. All the information was recorded in the fixed protocol. Collected data were classified, edited, coded and entered the computer for statistical analysis by using SPSS-23. Results: Out of 100 cases, 76.0% of participants belonged to age 21-40 years. The mean age was found 35.3±8.4 years with range from 18 to 62 years. Majority (95.0%) of participants were male with a ratio of 19:1. The majority (86.0%) of participants were exposed to sunlight ≤15 min/day. Only 3(3.0%) participants used sun block. More than three fourth (79.0%) of the participants used to eating sea fish (≥3 days per/weeks) followed by 52(52.0%) drink milk (≥3 days per/weeks) and 12(12.0%) was supplement with omega-3 fatty acid (fish oil). Majority 41(41.0%) of the participants had back pain followed by 12(12.0%) muscle cramp, 8(8.0%) neck pain and 8(8.0%) headache. Almost two third (65.0%) of the participants had deficiency, 31(31.0%) had insufficiency and 4(4.0%) had normal 25-hydroxyvitamin D. Significant association was also found between inadequate drinking milk with decreased 25-hydroxyvitamin D level. Conclusion: In conclusion 25-hydroxyvitamin D deficiency (65.0%) and insufficiency (31%) common among Bangladeshi workers coming from Middle East. It was influenced by their decreased sunlight exposure (≤15min/day) & clothing style. Inadequate consumption of milk and milk products may also play a role in decreasing vitamin D levels. J Rang Med Col. September 2024; Vol. 9, No. 2: 67-71